Royal Marine Commando 1950-82 from Korea to the Falklands - Fowler, Will 1947- (Warrior series, 2009)
One of the most prestigious and versatile units of the British armed forces, the Royal Marine Commandos were a specialized fighting force, serving in many theaters, including the Korean War (1950-1953), the Malayan Emergency (1947-1960), East Africa, Cyprus, Suez, Northern Ireland and the Faulklands, and performing a number of roles from counter-terrorism and counter-insurgency to conventional combined arms fighting. During the period covered in this account, conscription to the Royal Marines came to an end and the unit became a professional and dedicated force. The author provides a detailed look at the service life of a Royal Marine Commando in a time of great change, exploring the developments that took place in recruitment, training, equipment, weaponry, dress and tactical deployment in the post-World War II period. The elite nature of the Royal Marines is maintained by the toughness of the Commando entry course at Lympstone in Devon - where successful entrants are awarded the distinctive green Commando beret. One major aspect of the course is that squads should work together, supporting the weakest members - a key ethos that is explored in this fascinating story.